The Limits of Explanation: Testing the Internalization Theory of the Multinationial Enterprise - Buckley, Peter J. (Journal of International Business Studies, 1988)
The paper explores the difficulties of testing the internalization approach in the modern theory of the multinational enterprise. The structure of the theory is elaborated and the conclusion drawn that testing cannot occur at the most general theoretical level but that the theory requires careful restricting assumptions to be placed on it to allow rigorous testing. Several empirical circumstances would constitute refutation if they could be shown to hold. However, the use of unconventional cases or outliers does not constitute disproof. More rigour is required in formulating and testing the theory but the current verdict on the theory must be “not disproven”.